2008
DOI: 10.1371/journal.ppat.1000007
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon Response Inhibits HIV Particle Production by Induction of TRIM22

Abstract: Treatment of human cells with Type 1 interferons restricts HIV replication. Here we report that the tripartite motif protein TRIM22 is a key mediator. We used transcriptional profiling to identify cellular genes that were induced by interferon treatment and identified TRIM22 as one of the most strongly up-regulated genes. We confirmed, as in previous studies, that TRIM22 over-expression inhibited HIV replication. To assess the role of TRIM22 expressed under natural inducing conditions, we compared the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
228
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(250 citation statements)
references
References 78 publications
11
228
0
7
Order By: Relevance
“…TRIM22 has been shown to interfere with HIV-1 infection by either LTR promoter repression (Tissot & Mechti, 1995), inhibition of viral replication (Bouazzaoui et al, 2006) or reduction of particle production (Barr et al, 2008). Interestingly, the C-terminal SPRY domain of TRIM proteins is proposed to be involved in protein-protein interactions and RNA binding (Hilton et al, 1998;Ponting et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM22 has been shown to interfere with HIV-1 infection by either LTR promoter repression (Tissot & Mechti, 1995), inhibition of viral replication (Bouazzaoui et al, 2006) or reduction of particle production (Barr et al, 2008). Interestingly, the C-terminal SPRY domain of TRIM proteins is proposed to be involved in protein-protein interactions and RNA binding (Hilton et al, 1998;Ponting et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…TRIM22 (also known as Staf50) was first identified to be an IFN-induced human protein that represses transcription directed by the long terminal repeat (LTR) promoter region of human immunodeficiency virus type 1 (HIV-1) (Tissot & Mechti, 1995). Recently, TRIM22 has been reported to be a natural antiviral effector of both HIV-1 replication and particle production (Barr et al, 2008;Bouazzaoui et al, 2006). The effect of TRIM22 was abolished by mutation of amino acids Cys15 and Cys18 of its RING-finger domain, suggesting that functional ubiquitin ligase activity is required for TRIM22-mediated antiviral activities.…”
Section: Introductionmentioning
confidence: 99%
“…The possible candidates include other TRIM family protein(s), such as TRIM22 or TRIM21, or a cellular protease. TRIM22 was recently identified to affect HIV-1 production through interaction with HIV-1 Gag polyprotein, and like TRIM5␣rh-mediated late restriction, disruption of the RING motif ablates the late restriction activity of TRIM22 (15). Moreover, the type I interferon-responsive TRIM5 and TRIM22 genes share the enhancer region, suggesting a similar transcriptional regulation of the two proteins (16,20).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that a RING domain is required for the efficient interaction with HIV-1 Gag polyproteins. The block of HIV-1 entry appears to occur independently of the ubiquitin/proteasome system during the TRIM5␣rh-mediated post-entry restriction (9,14), although more recent studies have demonstrated that proteasome inhibitors can partially relieve the TRIM5␣-dependent inhibition of reverse transcription without affecting the restriction of HIV-1 nuclear entry (2,15). We examined the influence of proteasome inhibitors on the late restriction.…”
Section: Ring Domain Ismentioning
confidence: 99%
See 1 more Smart Citation